Outcomes of unplanned sarcoma excision: impact of residual disease. (1st March 2016) - Charoenlap, Chris; Imanishi, Jungo; Tanaka, Takaaki; Slavin, John; Ngan, Samuel Y.; Chander, Sarat; Dowsey, Michelle Maree; Goyal, Chatar; Choong, Peter F.M.
Abstract: This study aimed to compare the oncological results between unplanned excision (UE) and planned excision (PE) of malignant soft tissue tumor and to examine the impact of residual tumor (ReT) after UE. Nonmetastatic soft tissue sarcomas surgically treated in 1996–2012 were included in this study. Disease‐specific survival (DSS), metastasis‐free survival (MFS), and local‐recurrence‐free survival (LRFS) were stratified according to the tumor location and American Joint Committee on Cancer Classification 7th edition stage. Independent prognostic parameters were identified by Cox proportional hazard models. Two‐hundred and ninety PEs and 161 UEs were identified. Significant difference in oncological outcome was observed only for LRFS probability of retroperitoneal sarcomas (5‐year LRFS: 33.0% [UE] vs. 71.0% [PE], P  = 0.018). Among the 142 UEs of extremity and trunk, ReT in re‐excision specimen were found in 75 cases (53%). UEs with ReT had significantly lower survival probabilities and a higher amputation rate than UEs without ReT (5‐year DSS: 68.8% vs. 92%, P  < 0.001; MFS: 56.1% vs. 90.9%, P  < 0.001; LRFS: 75.8% vs. 98.4%, P  = <0.001; amputation rate 18.5% vs. 1.8%, P  = 0.003). The presence of ReT was an independent poor prognostic predictor for DSS, MFS, and LRFS with hazard ratios of 2.02 (95% confidence interval (CI), 1.25–3.26), 1.62 (95% CI, 1.05–2.51) and 1.94 (95% CI, 1.05–3.59), respectively. Soft tissue sarcomas should be treated in specialized centers and UE should be avoided because of its detrimental effect especially when ReT remains after UE. Abstract : Residual disease in unplanned excision of soft tissue sarcoma was a poor prognostic predictor for all oncological outcomes. Soft tissue sarcomas should be treated in specialized centers and unplanned excision should be avoided because of its detrimental effect especially when residual disease remains after unplanned excision.